Humic Substances: Possibility of New Therapeutic Application (Revista Brasileira Multidisciplinar, 2009)
Humic substances (HS) are heterogeneous molecular aggregates, which have no defined structure and constitute the principal fraction of natural organic matter. They can act as complexation agents, due to their high density of functional groups, and therefore directly influence the transport, accumulation, bioavailability and toxicity of different substances. Metals are important environmental pollutants, since they are widely used during human activities, and following release are not either chemically or biologically degraded. Treatment of acute poisoning in humans caused by potentially toxic metals has employed complexation agents such as ethylenediaminetetraacetic acid (EDTA) or -aminoacids. However, some limitations of these materials such as the lack of selectivity of EDTA and the high cost of -aminoacids have provided the incentive for a search for alternatives. Previous studies of the properties of HS indicate their possible use as an alternative to these chelanting agents.
Keywords: Humic substances; Potentially toxic metals; Chelating agents.